Perempuan dalam Iklan Pariwisata Indonesia - Arista Nur Widiastuti (MediaTor (Jurnal Komunikasi), 2018)
Research about gender in advertising has already done a lot, but it more focused on quantitative research. Tourism research being conducted because it relates to culture. Tourism ads showed tourism activities carried out by the community, included many different cultures in each area and this is also relates to social roles. This research is a descriptive qualitative research by using content analysis to examine about the portrayal of women in the tourism advertising. The study was conducted by the deductive approach of gender advertisment categorization according to Goffman. Categorization of Goffman (1979) consisted of Relative Size, Feminine Touch, Function Rank, The Ritualization of Subordination, The Family and  Licenced Withdrawal. The object of this research is Indonesia’s tourism ads uploaded in youtube accounts “ Indonesia.Travel”, since 2010, there are 211 videos uploaded on the account. The samples used for the research are 10 videos. The ads are taken with the technique of purposive and continued by random. The results showed that there is still a depiction of women who defended the role of traditional stereotype, but there are categories that is already starting to show the woman out of the role of stereotype.